"Hell You Talmbout?" Sighting confusion in the performance of Black Revolt. Issue 3 (1st September 2020) - Imhotep, Ra Malika; Zhang, SJ; Snorton, C. Riley
Abstract : This essay considers how "confusion" shapes narrative strategies and understandings of the 1811 Uprising in Louisiana and how artistic practice, performance, and amateur documentation differently refract public memory-making of the uprising and its brutal response. Here confusion also maps the relations between reenactment, the reenactors, and the practice and politics of abolitionist imagination.